ANALISIS FAKTOR-FAKTOR PENYEBAB RENDAHNYA MOTIVASI BELAJAR SISWA MTs NEGERI 1 TAPANULI TENGAH DISAAT PANDEMI COVID-19 - Sri Wahyuni Naibaho; Eva Yanti Siregar; Rahmatika Elindra (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2021)
The background of the study because at this time the world is troubled by the Covid -19 pandemic which has caused several countries to go into a massive lock down. Indonesia conducted PSBB (Large-Scale Social Restrictions) in several regions and conducted learning at home. The effect of learning at home is low learning motivation in pandemic Covid-19 period. The purpose of this study is to describe factors causing low motivation in pandemic Covid-19 period of students at MTs Negeri 1 Tapanuli Tengah. The approach of the research used qualitative descriptive and subject of the research is seventh grade students of MTs Negeri 1 Tapanuli Tengah which includes 24 students. Questionnaire and interview were used in collecting the data. The result of the research shows factors causing low learning motivation in pandemic Covid – 19 period of students at MTs Negeri 1 Tapanuli Tengah includes students’ dream or aspiration, students’ ability, students’ condition, students’ environment condition, and dynamic elements in teaching students.